The Role of Total Quality Management (TQM) in Improving the Health Services Provided at the Benghazi Medical Center (BMC) - Gadalla , Randa Mahmoud (Scientific Journal of University of Benghazi, 2020)
In healthcare settings, clients/patients urge for quality in services have been increasing. Quality and performance management in healthcare settings becomes more demanding due to lack of effective methods for enhancing performance leadership, accountability, managerial skills and poor strategic planning. This, therefore, warrants, effective quality management approach, such as Total Quality Management (TQM) , is implemented, assessed or monitored appropriately to improve competitiveness, effectiveness and flexibility.This descriptive study was conduct on ( 117 ) patients from various clinical departments of inpatients admitted to Benghazi Medical Center (BMC), Libya during period from Jun to March 2020. All patients were asked questions through the questionnaire form. The relative weight was used in the statistics to clarify the importance of each axis and its effect on the quality of service provision from the patients' point of view and attention to it through the total quality management.It was found that (87%) of patients were their length of stay from (2-9 days). The relative weight is the average of "receive it at the reception desk" (4.2), while is poor of "waiting room" (3.9). The patients ’opinion about radiological examinations and analyzes obtained with a moderate average relative weighted, and moderate service quality from patient opinion view .There is a low level of quality health services provided by public hospitals, and a deficiency in the service provided by the nursing towards the patients.